2011
DOI: 10.1111/j.1365-2885.2011.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic modelling of robenacoxib in a feline tissue cage model of inflammation

Abstract: Robenacoxib is a novel nonsteroidal anti-inflammatory drug developed for use in cats. It is a highly selective COX-2 inhibitor. Results from previous feline studies showed that, despite a short half-life in blood, the effect of robenacoxib persisted for 24 h in clinical studies. A tissue cage model of acute inflammation was used to determine robenacoxib's pharmacokinetics and its ex vivo and in vivo selectivity for COX-1 and COX-2 using serum TxB(2) and exudate PGE(2) as surrogate markers for enzyme activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 43 publications
(115 reference statements)
7
55
0
Order By: Relevance
“…Once daily dosing with robenacoxib provided good efficacy over the dosing interval. These results support previous findings that robenacoxib has a relatively long duration of action despite its short blood half life, explained by concentration and persistence at sites of inflammation [13]. …”
Section: Discussionsupporting
confidence: 92%
“…Once daily dosing with robenacoxib provided good efficacy over the dosing interval. These results support previous findings that robenacoxib has a relatively long duration of action despite its short blood half life, explained by concentration and persistence at sites of inflammation [13]. …”
Section: Discussionsupporting
confidence: 92%
“…Blood concentration time profiles were available from 83 cats. The demographics of the cats, dose/route of administration, and design of these studies (rich or sparse sampling strategy) are summarized in Table . Fourteen of these 83 cats received robenacoxib by both routes.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed its pharmacokinetic properties via different administration routes including, intravenous, subcutaneous and oral administration in the dog and cat (Jung et al, 2009;Pelligand et al, 2012). In dogs, robenacoxib showed good bioavailability after oral (84%) and subcutaneous (88%) administration with a short blood half-life of 1 h (Jung et al, 2009).…”
Section: Robenacoxibmentioning
confidence: 99%